KUALITAS KOMITE AUDIT MEMODERASI MASA PERIKATAN AUDIT DAN SPESIALISASI AUDITOR PADA KUALITAS KOMITE AUDIT - Putri, Desak Dyah Eka; Wiratmaja, I Dewa Nyoman (E-Jurnal Akuntansi; Vol 10 No 2 (2015), 2015)
The purpose of this research to determine effect of audit tenure, auditor specialization, and interaction both of variable to audit quality with quality of audit committee become moderated variable. This research is chosen basic industry and chemicals that listed on Indonesia Stock Exchange IDX) as object of research in period 2010-2013. The Purposive sampling method is used to selection of sample so obtained 52 samples of data. This research used Moderated Regression Analysis (MRA) as analysis technique to test hypotheses. Based on analysis it was found that positive effect of audit firm tenure on audit quality. Specialization auditors has negative effect on audit quality. Interaction variable between audit tenure with quality of audit committee is to lower audit quality. While interaction variable between specialization auditor with quality of audit committee is to increasing audit quality.
Keywords: Audit Tenure, Specialized Auditors, Audit Committee, Audit Quality